A READER RESPONSE APPROACH IN COLLABORATIVE READING PROJECTS TO FOSTER CRITICAL THINKING SKILLS - Pasaribu, Truly Almendo; Iswandari, Yuseva Ariyani (LLT Journal: A Journal on Language and Language Teaching, 2019)
Reading has become a major concern of EFL educators. Reading does not only help students learn foreign languages, but it is also believed that it has a strong link with critical thinking skills. A reader response approach in collaborative works, adapted from literary theory, is believed to be beneficial for the students. Therefore, this study aims at investigating the answers to these two questions: (1) how are the collaborative reader responses implemented in Critical Reading and Writing II? and (2) To what extent does reader response approaches promote students critical thinking skills? With these questions in mind, the researchers collect the data by involving 24 participants from CRW II (Critical Reading and Writing) class. The data gathered from classroom observations, online archives and students reflections are analyzed descriptively, using qualitative case study method. It is hoped that the implementation of this approach can be useful not only to improve students reading skills, but also to provide more opportunity for students to exercise their critical thinking skills.